(untitled) (Third Sector Social Economic Review, 2019)
This study centers on the short and long-term impacts of merger and acquisition announcements on acquirer firm shares. We employ event study and calendar-time portfolio approach for the short and the long-term analyses, respectively. Our findings reveal that, in the short-term, abnormal returns are possible particularly before and exactly at the announcement date, whereas only cumulative abnormal returns survive in following days. In the long-term, however, announcements do not possess a significant impact on firm value. Firm size matters for the short-term abnormal returns, but does not appear to be a significant factor in the long-term.